Negative practice–value correlations in the GLOBE data: Unexpected findings, questionnaire limitations and research directions - Taras, Vas; Steel, Piers; Kirkman, Bradley L (Journal of International Business Studies, 2010)
The study of culture and cultural values continues to be hotly debated among cross-cultural researchers worldwide. Starting with the seminal work of Kluckhohn and Strodtbeck, and Hofstede, and continuing with more recent efforts, researchers have continued to develop and empirically examine cultural value frameworks in an attempt to understand how cultural differences affect work-related behaviors and attitudes. The purpose of this commentary is to briefly describe the interesting – and counterintuitive – findings from the Global Leadership and Organizational Behavior Effectiveness (GLOBE) project, summarize the different interpretations of these findings offered by Maseland and van Hoorn, and by Brewer and Venaik, provide a critique of their arguments, and finally offer a list of possible alternative interpretations and explanations for the conflicting findings in the GLOBE study.